Association of different insulin resistance surrogates with all-cause and cardiovascular mortality among the population with cardiometabolic multimorbidity - Hongqiang Zhang; Zhixin Tu; Sihua Liu; Jumei Wang; Jie Shi; Xingyu Li; Rongdongqing Shi; Minghui Chen; Tong Yue; Sihui Luo; Yu Ding; Xueying Zheng (Cardiovascular Diabetology)
Abstract Background The coexistence of cardiometabolic diseases (CMDs), defined as cardiometabolic multimorbidity (CMM), has been shown to significantly elevate mortality risk. Insulin resistance (IR) is one of the main contributing factors to the pathogenesis of CMM. Although several surrogates for IR are employed in clinical evaluations, their relationship with mortality in individuals with CMM remains unclear. This study aimed to investigate the associations between various IR surrogates and mortality in individuals with CMM, and to evaluate their prognostic value. Methods This study enrolled 1093 patients diagnosed with CMM. We developed five surrogate markers to assess IR levels: triglyceride-glucose (TyG) index, TyG-waist circumference (TyG-WC), TyG-waist height ratio (TyG-WHtR), homeostatic model assessment of insulin resistance (HOMA-IR), and metabolic score for insulin resistance (METS-IR). To investigate the associations between different IR surrogates and both all-cause and cardiovascular mortality, multivariable Cox proportional hazards models were applied. We employed restricted cubic splines to examine non-linear associations, and Cox models were developed on either side of the inflection point for additional investigation. Meanwhile, the predictive values of five IR surrogates were further assessed. Results Of the 477 all-cause deaths that occurred during a median follow-up of 5.8 years, 197 were related to cardiovascular disease. Among five surrogate markers of IR, the TyG index was the only one that significantly correlates with both all-cause and cardiovascular mortality. The threshold value for both types of mortality was 8.85. A TyG index beneath the inflection point exhibits an inverse correlation with cardiovascular mortality (HR 0.483; 95% CI = 0.281–0.831) and all-cause mortality (HR 0.519; 95% CI = 0.368–0.732). On the other hand, when the TyG index surpassed the inflection point, it demonstrated a positive correlation with cardiovascular mortality (HR 1.413; 95% CI = 1.075–1.857) and all-cause mortality (HR 1.279; 95% CI = 1.070–1.529). Based on the analysis of receiver operating characteristics, the TyG index has been recognized as a dependable predictor of survival outcomes. Conclusions This study emphasizes the prognostic significance of IR surrogates, particularly the TyG index, in predicting mortality among individuals with CMM. The TyG index constitutes a crucial element in the development of management and intervention strategies for these patients. Graphical abstract